Aging kidney donors and recipients: risks and challenges. (October 2008) - Hartmann, Erica; Reeves-Daniel, Amber; Singh, Rajinder; Stratta, Robert J
Until recently, patients with end-stage renal disease were denied access to renal transplantation solely based on older age. In the 1990s, improvements in surgical techniques and immunosuppressive therapies led to increased access and acceptable rates of graft and patient survival for older and higher risk patients. More recently, efforts to meet the growing demand for transplantation have included the increased use of older donor organs. However, the increasing shift toward both older donors and recipients in kidney transplantation in the USA has led to new controversies and challenges. Transplant physicians are now faced with rationing a limited resource and maximizing long-term outcomes for recipients of all ages.